Introduction - Szilágyi, János Ede (Constitutional Protection of the Environment and Future Generations: Legislation and Practice in Certain Central European Countries, 2022)
An important element of the preface chapter is to provide a methodological basis for the chapters in the second part of the book, which review the constitutions and constitutional jurisprudence of the eight countries covered by the book. The national chapters of the book analyse the constitutions and practices of each country on the basis of nine main criteria.